Fabrication of iodine/nitrogen co‐doped three‐dimensional porous reduced graphene oxide for high energy density supercapacitors. (19th April 2022) - Xue, Songlin; Zhang, Piao; Liu, Bin; Liu, Jin; Yan, Qiong; Pan, Hongfei; Tu, Wenmao; Zhang, Haining
Summary: As an electrode for supercapacitor, the gravimetric specific capacitance of two‐dimensional layered graphene is theoretically superior to general porous carbon materials. However, the relatively low porosity and volumetric energy density of two‐dimensional graphene‐based electrode materials remain challenging for its practical application. Herein, iodine/nitrogen co‐doped three‐dimensional reduced graphene oxide (PGr) synthesized through the socking‐drying process and subsequent calcination is reported. In the presence of NH4 I and KI, the obtained PGr containing 2.9 wt.% of I element and 3.15 wt.% of N element possesses highly interconnected three‐dimensional hierarchically porous network among the layered structure and possesses a high specific surface area of 622.5 m 2 ·g −1 . Moreover, the synthesized PGr exhibits exceptional electrical conductivity and excellent capacitive characteristics, delivering 268 F·g −1 of high gravimetric specific capacitance in a three‐electrode system in KOH (6.0 mol·L −1 ). Furthermore, symmetric supercapacitor assembled from the synthesized PGr shows 9.46 Wh·kg −1 of specific energy density when the power density is 600 W·kg −1 and its initial capacitance retains 97.5% after 10 000 cycles of charging and discharging at 10 A·g −1 . In addition, the device utilizing ionic liquid as electrolyte delivers 32.9 and 46.2 Wh·kg −1 of specific energy density under 1.35 kW·kg −1 at 25°C and 1.85 kW·kg −1 at −50°C, respectively. Abstract : Iodine/nitrogen co‐doped three‐dimensional reduced graphene oxide (PGr) with a specific surface area of 622.5 m 2 ·g −1 was synthesized through socking‐drying process and subsequent calcination in the presence of NH4 I and KI. It delivers a high gravimetric specific capacitance of 268 F·g −1 in a three‐electrode system in 6.0 mol·L −1 KOH. Symmetric supercapacitor assembled from PGr with ionic liquid electrolyte delivers specific energy density of 32.9 Wh·kg −1 under 1.35 kW·kg −1 at 25°C and 46.2 Wh·kg −1 under 1.85 kW·kg −1 at −50°C.